2018
DOI: 10.1111/jfbc.12526
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol contents and antioxidants activities of biscuits produced from ginger-enriched pigeon pea-wheat composite flour blends

Abstract: This study investigated the phenolic content and antioxidant activities of biscuits produced from pigeon pea-wheat flour. Biscuits were produced by substituting wheat flour (WF) with pigeon pea flour (PP) in proportions of 100:0 (WF), 75:25 (25-PP), 50:50 (50-PP), 25:75 (75-PP), and 0:100 (100-PP) and fortified with ginger (4.5%). Aqueous extracts of flour and biscuit blends were prepared by dissolving each sample in distilled water (1:100 w/v), after which clear supernatant was obtained prior to analyses of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…The higher antioxidant capacity of the 36% DSSF biscuits can be explained by the higher TPC content, since high correlation between antioxidant capacity and phenolic compounds has been reported [31]. Similar results have been reported by Gbenga-Fabusiwa et al [32], who found that biscuits produced from pigeon pea–wheat flour had higher phenolic content and antioxidant activities compared to those produced with wheat flour only. Aksoylu et al [33] reported higher TPC in biscuits made with blueberry and grape seeds, while Ajila, Leelavathi and Rao [12] reported that biscuits with mango peel powder had higher DPPH activity.…”
Section: Resultssupporting
confidence: 77%
“…The higher antioxidant capacity of the 36% DSSF biscuits can be explained by the higher TPC content, since high correlation between antioxidant capacity and phenolic compounds has been reported [31]. Similar results have been reported by Gbenga-Fabusiwa et al [32], who found that biscuits produced from pigeon pea–wheat flour had higher phenolic content and antioxidant activities compared to those produced with wheat flour only. Aksoylu et al [33] reported higher TPC in biscuits made with blueberry and grape seeds, while Ajila, Leelavathi and Rao [12] reported that biscuits with mango peel powder had higher DPPH activity.…”
Section: Resultssupporting
confidence: 77%
“…The cream‐white seed varieties are abundant in sub‐Saharan Africa, although it is consumed less in the region compared to other pigeon pea‐producing regions, for example, South Asia (Odeny, ). Due to its physicochemical properties, pigeon pea flour has been used to enhance the nutritional value of wheat‐based baked goods (Gbenga‐Fabusiwa, Oladele, Oboh, Adefegha, & Oshodi, , ; Okpala & Okoli, ; Rampersad, Badrie, & Commissiong, ). Moreover, baked products formulated with pigeon pea flour are reported to have beneficial glycemic control and antidiabetic properties, which suggests potential use in managing type 2 diabetes mellitus (T2DM) (Gbenga‐Fabusiwa et al, ; Olagunju, Omoba, Enujiugha, & Aluko, ).…”
Section: Introductionmentioning
confidence: 99%
“…The high protein content of AYB makes it an important source of protein in the human diets of many tropical countries (Elsie and David, 2016). Furthermore, the high protein bean flour fractions could be substituted for wheat flour to produce good quality biscuits and bread in food industries (Gbenga-Fabusiwa et al, 2018b;Yusufu et al, 2016;Nneoma et al, 2012;Amakoromo et al, 2012). It could also be used in preparing porridge, moimoi and beans cake.…”
Section: Resultsmentioning
confidence: 99%